The effectiveness of Kangaroo Mother Care in hospitalization period of preterm and low birth weight infants: systematic review and meta-analysis - Narciso,Letícia M. (2022)
Abstract Objective: To evaluate the effectiveness of kangaroo mother care (KMC) in reducing the length of hospital stay of preterm and/or low birth weight infants. Source: Cochrane Library, Pubmed, Embase, LILACS, and Scielo. Randomized clinical trials without time or language limit were included. The intervention was the KMC in preterm and/or low birth weight infants born in health facilities compared to conventional care. The article selection was performed by a pair of reviewers independently. The methodological quality assessment was performed using the tool Risk of Bias 2. Summary of the findings: Eight hundred and sixty-four citations were identified and 12 were selected for data extraction. There was a reduction in the length of hospital stay in days in the KMC group compared to the conventional care group, with a statistically significant difference (MD -1.75, 95% CI -3.22 to -0.28). The subgroup that underwent the intervention for more than six hours daily did not show a statistical difference for the length of hospital stay outcome (MD -0.79, 95% CI -2.52 to 0.90), while the subgroup that underwent the intervention for less than six hours daily showed a reduction in this outcome with a statistically significant difference (MD -4.66, 95% CI -7.15 to -2.17). Conclusions: KMC is a safe and low-cost intervention that has been shown to be effective in reducing the length of hospital stay of preterm and/or low birth weight infants.